Benefit–Cost–Risk Based Selection of Biomass Co-Firing Feedstock for Coal-Fired Power Plants Using the Analytical Hierarchy Process - Disya Berliani Salsabila; Udisubakti Ciptomulyono (Interdisciplinary Social Studies, 2026)
The national energy transition encourages the application of biomass co-firing technology in Steam Power Plants (PLTU) as an effort to reduce greenhouse gas emissions and increase the renewable energy mix. The success of the implementation of co-firing is greatly influenced by the selection of the right biomass raw materials, considering the trade-off between benefits, costs, and operational risks. This study aims to determine the most optimal co-firing biomass raw materials in coal-fired power plants using the Benefit-Cost–Risk Analysis approach combined with the Analytical Hierarchy Process (AHP) method. The study was conducted on one of the coal-fired power plants in East Java by comparing three alternatives, namely sawdust, rice husks, and coal without co-firing. The weighting of criteria was carried out through expert assessment using AHP paired comparisons. The selected alternatives were then analyzed for their environmental impact using the Life Cycle Assessment (LCA) approach with the scope of cradle to gate. The results show that sawdust has the highest Benefit value, a Benefit–Cost (BCR) ratio above one, and a level of risk that can still be managed compared to other alternatives. The LCA analysis identified boiler units as the main hotspots of environmental impact, so operational improvements were recommended through water-steam system control. This research provides a basis for strategic decision-making in the selection of co-firing biomass that supports the energy transition and environmental sustainability.